Dyadic executive function effects in children's collaborative hypermedia learning. (April 2019) - Paans, Cindy; Segers, Eliane; Molenaar, Inge; Verhoeven, Ludo
Abstract: The current study investigated the extent to which executive functions (EF) affect how prior knowledge predicts hypermedia learning outcomes in primary school children. Learning outcomes were: individual knowledge and transfer, and dyadic assignment quality. Eighty-seven same-sex dyads participated in a hypermedia WebQuest assignment about the heart and living a healthy lifestyle. EF measures were action control and attention control. Dyadic analyses were performed using actor-partner interdependence models with dyads distinguished by EF. Analyses showed that one's own pre-test predicted one's own and partner's post-test for both higher and lower EF dyad members. Furthermore, for dyad members with relative higher EF only, their own and partner's pre-test predicted transfer. Finally, the lower action control dyad member's pre-test and the higher attention control dyad member's pre-test predicted assignment quality. These results show the importance of EF and prior knowledge for deeper conceptual understanding in a collaborative learning setting. Highlights: Pre-test predicted post-test for oneself and one's dyadic partner independent of EF. Pre-test of both dyad members predicted transfer of relative higher EF members. Pre-test did not predict transfer of relative lower EF dyad members. The higher attention control dyad member's pre-test predicted assignment quality. The lower action control dyad member's pre-test predicted assignment quality.